Perencanaan Biaya Pembuatan Dan Proses Pemesinan Mesin Pengemas Minyak Goreng Sachet - Iwan Nugraha; Jojo Sumarjo; M. Topan Maulana (Fakultas Teknik UMSU, 2021)
The packaging is an activity that aims to increase selling value and protect products from damage from the environment. Packaging automatically uses a packaging machine to increase the amount of production. Packaging machines have very expensive prices so that it is burdensome for UMKM who want to do business in this field. This research will make a cooking oil packaging machine with a capacity of 15 pcs / minute. Making this machine requires a machining process including the welding process, the grinding process, the drilling process, and the lathe process. The cooking oil packaging machine consists of several components and in the manufacturing of the components, this packaging machine costs Rp. 197,513, shaft component Rp. 130,506, press components Rp. 150,085, plastic forming components Rp. 50,631, oil channel components Rp. 50,591. The basic price of this cooking oil packaging machine is Rp. 2,713,000 and the price of the cooking oil packaging machine if added with VAT and the profit, the selling price of this machine is Rp. 4,609,000.